Congenital complete atrioventricular block. - Kertesz, N J (1997)
Congenital complete atrioventricular block is found in 1 of 22,000 live births. Over time, it has become apparent that these patients represent not a single distinct disease process, but several processes with the common manifestation of atrioventricular block. The evaluation of these patients to determine their risk of sudden death and need for pacing is not well defined.